Impact of selenium on the intestinal microbiome-eCBome axis in the context of diet-related metabolic health in mice - Guevara Agudelo, Fredy Alexander; Leblanc, Nadine; Bourdeau-Julien, Isabelle; St-Arnaud, Gabrielle; Lacroix, Sébastien; Martin, Cyril; Flamand, Nicolas; Veilleux, Alain; Di Marzo, Vincenzo; Raymond, Frédéric (Frontiers in Immunology, 2022)
Dietary micronutrients act at the intestinal level, thereby influencing microbial communities, the host endocannabinoidome, and immune and anti-oxidative response. Selenium (Se) is a trace element with several health benefits. Indeed, Se plays an important role in the regulation of enzymes with antioxidative and anti-inflammatory activity as well as indicators of the level of oxidative stress, which, together with chronic low-grade inflammation, is associated to obesity. To understand how Se variations affect diet-related metabolic health, we fed female and male mice for 28 days with Se-depleted or Se-enriched diets combined with low- and high-fat/sucrose diets. We quantified the plasma and intestinal endocannabinoidome, profiled the gut microbiota, and measured intestinal gene expression related to the immune and the antioxidant responses in the intestinal microenvironment. Overall, we show that intestinal segment-specific microbiota alterations occur following high-fat or low-fat diets enriched or depleted in Se, concomitantly with modifications of circulating endocannabinoidome mediators and changes in cytokine and antioxidant enzyme expression. Specifically, Se enrichment was associated with increased circulating plasma levels of 2-docosahexaenoyl-glycerol (2-DHG), a mediator with putative beneficial actions on metabolism and inflammation. Others eCBome mediators also responded to the diets. Concomitantly, changes in gut microbiota were observed in Se-enriched diets following a high-fat diet, including an increase in the relative abundance of Peptostreptococcaceae and Lactobacillaceae. With respect to the intestinal immune response and anti-oxidative gene expression, we observed a decrease in the expression of proinflammatory genes Il1β and Tnfα in high-fat Se-enriched diets in caecum, while in ileum an increase in the expression levels of the antioxidant gene Gpx4 was observed following Se depletion. The sex of the animal influenced the response to the diet of both the gut microbiota and endocannabinoid mediators. These results identify Se as a regulator of the gut microbiome and endocannabinoidome in conjunction with high-fat diet, and might be relevant to the development of new nutritional strategies to improve metabolic health and chronic low-grade inflammation associated to metabolic disorders.